Plucked piezoelectric biomorphs for energy harvesting applications - Pozzi, Michele; Zhu, Meiling (Cranfield University, 2011)
The modern drive towards mobility and wireless devices is motivating intense research in energy harvesting (EH) technologies. In an effort to reduce the battery burden of people, we are investigating a novel piezoelectric wearable energy harvester. As piezoelectric EH is significantly more effective at high frequencies, in opposition to the characteristically low-frequency human activities, we propose the use of an up-conversion strategy analogous to the pizzicato musical technique. In order to guide the design of such harvester, we have modelled with Finite Elements (FE) the response and power generation of a piezoelectric bimorph while it is "plucked", i.e. deflected, then released and permitted to vibrate freely. An experimental rig has been devised and set up to reproduce the action of the bimorph in the harvester. Measurements of the voltage output and the energy dissipated across a series resistor are reported and compared with the FE predictions. As the novel harvester will feature a number of bimorphs, each plucked tens of times per step, we predict a total power output of several mW, with imperceptible effect on the wearer's gait.